Cutaneous leishmaniasis in French Guiana: revising epidemiology with PCR-RFLP - Simon, Stephane (Trop Med Health, 2017)
BACKGROUND: The development of polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) technique for species identification among patients presenting leishmaniasis allowed to better determine the main circulating species in French Guiana. METHODS: A descriptive study of the Leishmania species was identified, and their spatiotemporal distribution was conducted using patient records between 2006 and 2013, with 1017 new cases of leishmaniasis diagnosed. Identification was realized by PCR-RFLP on 745 cases. RESULTS: The average proportions for different species were 86.2% for Leishmania (Vianna) guyanensis; 9.7% for Leishmania (Vianna) braziliensis; 2.8% for Leishmania (Leishmania) amazonensis; and 1.3% for Leishmania (Vianna) lainsoni, and no case of Leishmania (Vianna) naiffi was identified. Over this period, the proportion of cases due to L. (V.) braziliensis seemed to increase from 8.9% in 2006 to 13.0% in 2013 notably near the gold mining zones. CONCLUSIONS: The use of molecular tools has transformed the view of the local epidemiology of cutaneous leishmaniasis in French Guiana.